RELATIONSHIP BETWEEN FIRST OVULATION AND PREGNANCY OUTCOME IN EARLY POSTPARTUM DAIRY COWS - VETRIVEL, K; ANTOINE, D; MURUGAVEL, K; KANTHARAJ, S (The Indian Journal of Animal Reproduction, 2023)
The aim of the study was to investigate the relationship between the first postpartum ovulation and subsequent fertility in dairy cows. Forty HF crossbred cows were subjected to ultrasonography examination of ovaries at 72 hours interval from day 7 to 60 days postpartum. Ovulation was confirmed by the disappearance of the dominant follicle that had been detected at the previous examination and subsequent CL formation. The cows which were ovulated between 10 to 26 (21 ± 1.56) days postpartum were conceived within 90 days.